Pesan Sosial Tindak Tutur Mengeluh Tokoh Mamak dalam Novel Persiden Karya Wisran Hadi - Yustitiayu Novelly; Vivi Indriyani (Indonesian and Regional Language and Literature Department, Universitas Negeri Padang, 2024)
The role of mamak in Minangkabau customs has changed along with the development of social dynamics. This study aims to explain the social message in the speech act of complaining expressed by the character Mamak in the novel President by Wisran Hadi. This study uses a qualitative approach with a content analysis method. Data in the form of words, sentences, and dialogues containing the speech act of complaining by the character Mamak were collected through reading, marking, and recording techniques. Data analysis was carried out by identifying the speech act of complaining, connecting it to the context of the speech, and interpreting the speaker's intent. The results of the study showed that there were 38 speech acts of complaining expressed by the character Mamak. These speech acts convey social messages related to the shifting role of mamak in Minangkabau customs, such as the lack of appreciation from younger sisters, the neglect of the role of mamak in customary matters that are the responsibility of men, and the weakening position of mamak in the Minangkabau social structure. Thus, through the speech of the character Mamak, the author conveys social criticism of the changes in customary values ​​that occur in society. The implications of this study indicate that literature can be a reflective medium in understanding socio-cultural changes, especially in Minangkabau society.